Behavioral economic phenomena in decision-making for others - Ifcher, John; Zarghamee, Homa (Journal of economic psychology, 2020)
•In a lab experiment we test whether 7 behavioral biases apply in decision making for others (DMfO).•Willingness to pay is higher in DMfO than in decisions for oneself in three tasks.•Propensity to give uninterpretable responses is higher in DMfO than in decisions for oneself.•Subjects treat DMfO more like decisions for themselves when decisions for themselves precede DMfO.•Very few subjects report motivations that can be construed as rivalrous. We examine whether biases identified in the behavioral-economics literature apply in decision-making for others (DMfO). We conduct a laboratory experiment in which subjects make decisions on behalf of themselves and others in eighteen tasks that measure the following biases: present-bias in time preferences, reflection effect in risk preferences, compound risk aversion, decoy effect, anchoring bias, endowment effect, and identifiable-victim bias. In our experiment, DMfO is DMfO simpliciter: unincentivized decisions made by one individual on behalf of another–the individual making decisions faces no direct costs or benefits when engaging in DMfO (as she would in a principal-agent framework or with bequest motives), and DMfO is not framed as giving advice or guessing others’ behavior. Although we find that DMfO is by and large statistically indistinguishable from decisions for oneself, we identify the following self-other discrepancies: (i) willingness to pay (i.e., bids to procure goods and donations to charity) is higher in DMfO than in decisions for oneself in tasks associated with the anchoring bias, end owment effect, and identifiable-victim bias; and (ii) the propensity to give uninterpretable responses is higher in DMfO than in decisions for oneself. We also find order effects, with DMfO more similar to decisions for oneself when DMfO follows decision making for oneself. Lastly, in response to open-ended items soliciting self-reports of subjects’ approach to DMfO, most subjects report having followed some version of the “Golden Rule” (e.g., deciding for others as they would for themselves) or having tried to maximize the other subject’s payment or utility; very few subjects report motivations that can be construed as rivalrous.